Evaluating House’s (2015) Model for Professional Translation Quality Assessment - Raneen Aed Rasheed Khider; Alya’ Mohammed Hussein Ahmed Al-Rubai’i (Zanco Journal of Human Sciences, 2026)
Translation quality assessment models have been a central focus in the field of applied translation studies. They systematically assess translations by examining key aspects of translation quality, such as accuracy, fluency, terminology, style, and grammar. This study aims to evaluate the effectiveness, strengths, and weaknesses of House’s (2015) model. The model, widely recognized as it is highly influential in translation quality assessment, has not been evaluated for its broader effectiveness and limitations. It was originally tested by House herself to a limited number of English-German text samples only. This lack of comprehensive evaluation leaves an important gap in understanding its applicability and workability in practice. The research methodology involved selecting six English translated into Arabic. These translated texts were assessed according to House’s (2015) model criteria, followed by an evaluation of the model through a structured questionnaire by professional evaluators. Both quantitative and qualitative methods were adopted to analyze the data. The findings showed that House’s (2015) model was effective, reliable, and suitable for analyzing both literary and non-literary text types. It offered a comprehensive approach to assessing translation quality by taking into account linguistic, contextual, and functional elements, and provides a structured framework for evaluating various text types.